Cultural Wounding, Healing, and Emerging Ethnicities - Kearney, A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Today, there is new appeal in the analysis of ethnicity, not merely as innate and fixed identities or fragmented and lost identities, but rather as wounded and then creatively reclaimed. Kearney discusses international examples of cultural wounding and healing and presents two close readings of emerging ethnicities in Australia and Brazil.
Keywords: Ethnology; Ethnography; Anthropology; Ethnicity; Sociology; Social Anthropology; Cultural Anthropology; Ethnography; Anthropology; Ethnicity Studies; Sociology, general